Developing Guidebook for Visitors of Bentar Beach to Improve Their Experience - Bima Indra Pangestu (UPT P2M Politeknik Negeri Malang, 2021)
Vocational college students need to always upgrade their skills to be able to catch up with the demand of theindustry in which they would work. One way of doing it is by practicing their skills based on the learned theories and the guide of relevant expert advisor. The project is research and development. Developing Guidebook for visitors of Bentar Beach to Improve Their Experience is my final project. The guidebook is needed to find out interesting places in Bentar Beach tourist attractions, and also to know the history of Bentar Beach tourist attractions. The project was based on a preliminary study conducted in Bentar Beach Probolinggo. The project focused on developing a guidebook in bilingual, Englishand Indonesian versions, which can help foreign and domestic tourists to get to Bentar Beach easily. In developed this product, the writer adapted procedure of making guidebook from Richey & Klein (2014). In conducting this final project, the writer applied the language and writing skills that got in English Study Program, State Polytechnic of Malang. This research findings are especially beneficial for developing guidebook and students of D3 Program in Applied English at State Polytechnic of Malang. The findings offer possible solutions for similar problems they encounterduring making a guidebook.